Diseño y evaluacion de una herramienta para agilizar la cosecha manual de cafe - Oliveros T, C.E.=700 1 Ramirez G, C.A.; Buenaventura A, J.D.; Sanz U, J.R.
(En, Es)
ilus., 10 ref.
Keywords: CAFE; EQUIPO; DISEÑO; RECOLECCION; COSECHA; COLOMBIA; FLUJO DE COSECHA